Analisis Ergonomi Tempat Wudhu Masjid di Kota Banda Aceh Berdasarkan Antropometri - Hasballah Hasballah; Teuku Yasvi Ramadhana (Jurnal Teknik Mesin Unsyiah, 2020)
Wudu is a routine activity carried out by Muslims before performing the prayer, and mosques are the most frequently visited places for performing prayers. A mosque is a social facility of a city or region. The comfort of a mosque is an important factor in seeing the comfort of a city or region. The wudu facility is the main facility in a mosque that needs attention, an ergonomic wudu facility will provide comfort for visitors. The city of Banda Aceh, as the capital of Aceh province, holds the status of an Islamic Sharia region, it is important to provide social facilities such as a mosque that provide a sense of comfort for its residents and visitors. The wudu facility from mosques in the city of Banda Aceh is relevant to be researched and discussed to see the level of comfort. From 20 samples of mosques in Banda Aceh City that has observed, it was found that in general the mosques in the city of Banda Aceh do not yet have wudu facility that meet design standards in accordance with the ergonomic concept. There are only 2 mosques (10%) found where wudu facility meets the standard ergonomic design, and even then, it is only for the standing position of wudu facility. In general, the dimensions of the wudu facility that meet the ergonomic design standards are the height of the faucets from the floor, while the distance between the faucets and the distance between the faucets and the standing / sitting position does not meet the standard. This is a note for the Banda Aceh City Government to pay more attention to the services of social facilities in its region, so that improvements can be made in the future.